Method for preparing bone-like hydroxyapatite nano-whiskers through biological template induction, prepared bone-like hydroxyapatite nano-whiskers and application of bone-like hydroxyapatite nano-whiskers

Through the surface modification technology combined with biotemplate induction preparation method and ultrasonic microwave treatment, the problem of insufficient mechanical properties and biological activity of hydroxyapatite materials in the prior art was solved, and bone-like hydroxyapatite nanowhiskers with excellent mechanical properties and biocompatibility were prepared, which is suitable for bone repair and regeneration materials.

CN119710927APending Publication Date: 2025-03-28NINGBO BAOTING BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925474.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The hydroxyapatite materials prepared in the prior art have shortcomings in mechanical properties, degradation rate and antibacterial properties, and cannot achieve high mechanical properties, high biological activity and antibacterial properties at the same time.

Method used

Through the biological template induction preparation method, ultrasonic microwave treatment and surface modification technology were used to prepare bone-like hydroxyapatite nanowhiskers. The method includes dispersing whisker-like biological macromolecules, mixing phosphate and calcium salt solutions, adjusting pH, and promoting hydroxyapatite nucleation growth by ultrasonic microwave treatment. Subsequently, a surface modification treatment is performed to improve the mechanical properties and biocompatibility of the material.

Benefits of technology

The prepared bone-like hydroxyapatite nanowhiskers have excellent mechanical properties and biocompatibility, which can significantly improve the ability of cell adhesion, proliferation and differentiation, and their performance is close to that of human bone, and is suitable for bone repair and regeneration materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710927A_ABST
    Figure CN119710927A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing bone-like hydroxyapatite nanowhiskers through biological template induction, the prepared bone-like hydroxyapatite nanowhiskers and application, and belongs to the technical field of high-performance biological materials. The method for preparing the bone-like hydroxyapatite nanowhiskers through biological template induction comprises the following steps: performing dispersion treatment on whisker-shaped biological macromolecules to obtain a whisker-shaped biological template; the preparation method comprises the following steps: mixing a phosphate solution with a calcium salt solution, adjusting the pH value to obtain a precursor solution, mixing the precursor solution with a whisker-shaped biological template, and carrying out ultrasonic microwave treatment to obtain hydroxyapatite nanowhiskers; and carrying out surface modification treatment on the hydroxyapatite nano crystal whisker to obtain the bone-like hydroxyapatite nano crystal whisker. The bone-like hydroxyapatite nanowhisker prepared by the method has excellent mechanical properties and biocompatibility, the interaction between the bone-like hydroxyapatite nanowhisker and cells is enhanced, and the adhesion, proliferation and differentiation capabilities of the cells are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance biomaterials, and more specifically to a method for preparing bone-like hydroxyapatite nano whiskers by inducing a biological template, the prepared bone-like hydroxyapatite nano whiskers and their application. Background Art

[0002] With the aging of the population and the increase in accidental injuries such as traffic accidents, the demand for the repair of fractures and bone defects continues to rise. Traditional methods such as metal implants and autologous bone transplantation have many limitations, such as immune rejection, donor site pain and infection risks. Hydroxyapatite, an inorganic material with similar composition to human bone tissue, has been widely studied and applied in the field of bone repair due to its excellent biocompatibility, osteoinductivity and osteoconductivity. Hydroxyapatite interacts well with bone cells, promoting the adhesion, proliferation and differentiation of bone cells and accelerating the healing process of bone tissue.

[0003] At present, various preparation techniques of hydroxyapatite for bone repair engineering have been developed, such as precipitation method, hydrothermal method, etc., but due to its poor mechanical properties, mismatched degradation rate and lack of antibacterial properties, it is greatly limited in practical applications. In order to overcome the limitations of hydroxyapatite, researchers have conducted a variety of modification studies, including surface modification, morphology control, composite material preparation, etc. For example, the surface properties of hydroxyapatite are improved by plasma treatment, chemical modification and other methods to enhance its interaction with cells. "Journal of Applied Polymer Science" (2020, 137, 49293) proved that surface modification of hydroxyapatite (HA) with mono-substituted and di-substituted fatty acids (FAs) can significantly improve the mechanical properties of PLA / HA composite scaffolds, which is expected to be used in bone regeneration engineering. Nanostructured hydroxyapatite, such as nanowhiskers, nanorods and nanosheets, has attracted attention due to its larger specific surface area and higher surface energy. These nanostructures can provide more active sites, promote cell adhesion and growth, and improve the mechanical strength of the material. "Ceramics International" (Issue 22, 2022, page 33628) reported that hydroxyapatite nanorods of different sizes can be synthesized by adjusting the temperature of the hydrothermal method, and nanorods similar in size to human bones are compounded with polycaprolactone (PCL) scaffolds, ultimately improving the bioactivity and mechanical properties of the scaffold. In response to the problem of hydroxyapatite's lack of antibacterial properties, researchers have developed a variety of antibacterial hydroxyapatite composites by doping with antibacterial elements such as silver and zinc or compounding with antibacterial polymers to give hydroxyapatite antibacterial properties and reduce the risk of postoperative infection. Despite this, the hydroxyapatite prepared in the prior art has a single performance and cannot combine antibacterial properties, high mechanical properties, and high biological activity. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing bone-like hydroxyapatite nanowhiskers by bio-template induction, the prepared bone-like hydroxyapatite nanowhiskers and their applications. The prepared bone-like hydroxyapatite nanowhiskers have excellent mechanical properties and biocompatibility, and enhance the interaction between bone-like hydroxyapatite nanowhiskers and cells, thereby improving the ability of cells to adhere, proliferate and differentiate.

[0005] The purpose of the present invention is to provide a method for preparing bone-like hydroxyapatite nano whiskers by biological template induction, comprising the following steps:

[0006] The whisker-shaped biomacromolecules are dispersed to obtain a whisker-shaped biotemplate.

[0007] After mixing a phosphate solution and a calcium salt solution, adjusting the pH to 7-8 to obtain a precursor solution, mixing the precursor solution with a whisker-shaped biological template, and then performing ultrasonic microwave treatment, during which hydroxyapatite nucleates and grows to obtain hydroxyapatite nano whiskers.

[0008] The hydroxyapatite nano whiskers are subjected to surface modification treatment to improve the mechanical properties of the hydroxyapatite nano whiskers, thereby obtaining bone-like hydroxyapatite nano whiskers.

[0009] For example, the pH value is 7, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0010] In a preferred embodiment of the present invention, the mass ratio of the calcium salt to the whisker-like bio-template is 10 to 50:1. For example, the mass ratio of the calcium salt to the whisker-like bio-template is 10:1, 20:1, 30:1, 40:1, 50:1, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable.

[0011] In a preferred embodiment of the present invention, the molar ratio of phosphorus to calcium in the precursor solution is 1:0.5-2; for example, the molar ratio of phosphorus in the phosphate solution to calcium in the calcium salt solution is 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.

[0012] The concentration of the calcium salt solution is 0.01mol / L to 1mol / L. For example, the concentration of the calcium salt solution is 0.01mol / L, 0.03mol / L, 0.05mol / L, 0.07mol / L, 0.09mol / L, 0.1mol / L, 0.3mol / L, 0.5mol / L, 0.7mol / L, 0.9mol / L, 1mol / L, etc.

[0013] The concentration of the phosphate solution is 0.02mol / L to 2mol / L, and the concentration of the phosphate solution is 0.02mol / L, 0.04mol / L, 0.06mol / L, 0.08mol / L, 0.1mol / L, 0.2mol / L, 0.4mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.6mol / L, 1.8mol / L, 2mol / L, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are equally applicable.

[0014] In a preferred embodiment of the present invention, the ultrasonic frequency of the ultrasonic microwave treatment is 100kHz to 160kHz, for example, the ultrasonic frequency is 100kHz, 110kHz, 120kHz, 130kHz, 140kHz, 150kHz, 160kHz, etc.

[0015] The microwave power is 600W to 1000W, for example, the microwave power is 600W, 700W, 800W, 900W, 1000W, etc.

[0016] The processing temperature is 100°C to 240°C, and the processing temperature is 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, etc.

[0017] The processing time is 5 min to 48 h, for example, the processing time is 5 min, 0.5 h, 1 h, 4 h, 10 h, 20 h, 36 h, 48 h, etc.

[0018] The reaction pressure is 1 MPa to 5 MPa, for example, the reaction pressure is 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0019] In a preferred embodiment of the present invention, the surface modification treatment is at least one of nitrogen plasma treatment, silane coupling agent treatment, citric acid and stearic acid modification, heat treatment and metal nanoparticle doping.

[0020] In a preferred embodiment of the present invention, the biomacromolecule is pancreatic islet fiber, chain DNA or linear virus.

[0021] In a preferred embodiment of the present invention, the calcium salt is at least one of calcium phosphate, calcium hydrogen phosphate, calcium dihydrogen phosphate, calcium chloride, calcium nitrate and calcium disodium ethylenediaminetetraacetate.

[0022] In a preferred embodiment of the present invention, the phosphate is at least one of potassium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, calcium hydrogen phosphate and calcium phosphate.

[0023] The second object of the present invention is to provide bone-like hydroxyapatite nanowhiskers prepared by the above preparation method.

[0024] The third object of the present invention is to provide the use of the above-mentioned bone-like hydroxyapatite nanowhiskers in the preparation of bone repair materials and bone regeneration materials.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention adopts a specific whisker-like biological template, and induces the growth of nano whiskers by an ultrasonic external field and microwave combined with an assisted biomimetic synthesis method, thereby obtaining a bone-like nanostructured material with excellent mechanical properties and biocompatibility; at the same time, by setting the synthesis step and the post-processing step, the crystallinity and mechanical strength of the nano whiskers are improved to meet the application requirements of bearing a large load; surface modification technology is used to improve the surface characteristics of the nano whiskers, improve the mechanical properties, enhance its interaction with cells, and improve the ability of cell adhesion, proliferation and differentiation. In summary, the structure, composition and performance of the hydroxyapatite nano whiskers that can be prepared by this method are close to those of human bones, greatly improving the mechanical strength and biological activity of hydroxyapatite materials in medical environments, matching the absorption and growth rate of human bones, and having broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the technical roadmap of the present invention.

[0028] Figure 2 This is the SEM image of the hydroxyapatite nanowhiskers with bone-like structure prepared in Example 2. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] A method for preparing bone-like hydroxyapatite nanowhiskers induced by biological templates, such as Figure 1 As shown, the following steps are included:

[0031] S1. Dispersing whisker-shaped biomacromolecules to obtain whisker-shaped bio-templates.

[0032] S2. After mixing the phosphate solution and the calcium salt solution, the pH is adjusted to 7-8 to obtain a precursor solution. After mixing the precursor solution with the whisker-shaped biological template, ultrasonic microwave treatment is performed to obtain hydroxyapatite nano whiskers.

[0033] S3, performing surface modification treatment on the hydroxyapatite nanowhiskers to obtain bone-like hydroxyapatite nanowhiskers.

[0034] The present invention forms whisker-shaped biological templates by pre-treating biological macromolecules (such as DNA, pancreatic islet fibers or tobacco mosaic virus TMV, etc.), and these whisker-shaped templates help the nucleation and growth of hydroxyapatite nano whiskers. Then, the whisker-shaped biological templates are mixed with phosphate and calcium salt solutions (such as potassium dihydrogen phosphate and calcium phosphate, etc.), and a pH regulator (such as Tris or PBS) is used to adjust the pH value of the mixed solution to between 7.0 and 8.0. In this process, the calcium salt and the phosphate undergo a chemical reaction to form a precursor of hydroxyapatite.

[0035] Subsequently, ultrasound and microwave technology are used to provide energy to promote the nucleation and growth of hydroxyapatite to form nano whiskers with a specific aspect ratio. These technologies can increase the reaction rate, enhance the crystallinity of the material, and help control the size and morphology of the nano whiskers. Ultrasound and microwave assistance can also solve the problem of powder agglomeration to a certain extent, and improve the uniformity and dispersibility of the obtained nano hydroxyapatite. Finally, the surface properties of the nano whiskers are improved by surface treatment technology (such as nitrogen plasma treatment, silane coupling agent treatment, etc.), providing mechanical properties, especially hardness, and enhancing its interaction with cells, thereby improving the ability of cell adhesion, proliferation and differentiation. This step is crucial for improving the biological activity of hydroxyapatite nano whiskers. Through this series of steps, the prepared hydroxyapatite nano whiskers have excellent mechanical properties and biocompatibility, and are suitable for use in bone repair and regenerative medicine.

[0036] In a preferred embodiment of the present invention, the mass ratio of calcium salt to whisker-shaped bio-template is 10-50:1.

[0037] In a preferred embodiment of the present invention, the molar ratio of phosphorus in the phosphate solution to calcium in the calcium salt solution is 1-2:1-1.5; the concentration of the calcium salt solution is 0.01 mol / L-1 mol / L, and the concentration of the phosphate solution is 0.02 mol / L-2 mol / L.

[0038] In a preferred embodiment of the present invention, the reaction temperature of the surface modification treatment is 100° C. to 350° C., and the reaction time is 5 h to 20 h.

[0039] In a preferred embodiment of the present invention, the ultrasonic frequency of the ultrasonic microwave treatment is 100kHz to 160kHz, the microwave power is 600W to 1000W, the treatment temperature is 100℃ to 240℃, and the treatment time is 5min to 48h. The hydroxyapatite nanowhiskers with a specific aspect ratio are synthesized by combining the ultrasonic field and microwaves; the performance is best when the aspect ratio of the prepared hydroxyapatite nanowhiskers is closest to that of human bones. The higher the parameters in the ultrasonic microwave treatment process, the stronger the ultrasonic microwave, the greater the energy, the more nuclei are formed, and the larger the size.

[0040] When performing ultrasonic microwave treatment, the instrument used is at least one of a microwave ultrasonic synergistic extractor, a microwave ultrasonic synergistic cell lyser, a microwave ultrasonic synergistic crusher, a microwave ultrasonic chemical reactor and a microwave ultrasonic synergistic digester.

[0041] In a preferred embodiment of the present invention, the biomacromolecules are pancreatic islet fibers, chain DNA, and tobacco mosaic virus TMV linear structure macromolecules.

[0042] The pretreatment process in step S1 is at least one of the following treatment methods: adjusting pH, high pressure homogenization, heating and stirring, and centrifugation to form a whisker-shaped biological template. The mass concentration of the biological macromolecules in the pretreatment aqueous solution is 0.1-10%.

[0043] In a preferred embodiment of the present invention, the calcium salt is at least one of calcium phosphate, calcium hydrogen phosphate, calcium dihydrogen phosphate, calcium chloride, calcium nitrate, and calcium disodium edetate.

[0044] In a preferred embodiment of the present invention, the phosphate is at least one of potassium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate.

[0045] In a preferred embodiment of the present invention, in S2, a pH regulator is used to adjust the pH, and the pH regulator is at least one of tris(hydroxymethyl)aminomethane hydrochloride [Tris], phosphate buffered saline (PBS), 3-morpholinopropanesulfonic acid (MOPS), 4-hydroxyethylpiperazineethanesulfonic acid (2-[4-(2-hydroxyethyl)piperazin-1-yl]ethanesulfonic acid, HEPES), tris(hydroxymethyl)methylglycine (Tricine), ammonia-ammonium chloride, and acetic acid.

[0046] In a preferred embodiment of the present invention, the surface treatment method in S3 is at least one of nitrogen plasma treatment, silane coupling agent treatment, citric acid and stearic acid modification, heat treatment at 100°C to 350°C for 5-20h, and metal nanoparticle doping.

[0047] The calf thymus double-stranded DNA molecule used in the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a CAS number of 91080-16-9. Bovine insulin was purchased from Beijing Ruida Henghui Technology Development Co., Ltd., with a CAS number of 11070-73-8.

[0048] The wild-type TMV used in the present invention has been disclosed in "Fabrication and characterization of CdS nanowires template in tobacco mosaic virus with improved photocatalytic ability" published in Applied Microbiology and Biotechnology.

[0049] Example 1

[0050] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0051] S1. Preparation of whisker-shaped bio-template: 250 ml of calf thymus double-stranded DNA molecules with a mass concentration of 0.1% were homogenized under high pressure at 50 MPa and 25° C., dissolved in 250 ml of water, and heated and stirred at 50° C. for 1 h to form a transparent solution to obtain a whisker-shaped bio-template.

[0052] S2. Preparation of hydroxyapatite with bone-like structure: mix 250 mL of 0.01 mol / L calcium phosphate solution and 75 mL of 0.02 mol / L potassium dihydrogen phosphate solution, adjust the pH to 7.0 using Tris as a pH regulator, and use a microwave ultrasonic synergistic extractor with a microwave power of 800 W and an ultrasonic frequency of 120 kHz at 100°C and a reaction pressure of 1 MPa for 20 minutes. Dry and grind to obtain hydroxyapatite with bone-like structure.

[0053] S3. Preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: Place hydroxyapatite in an electrode vacuum chamber and treat it at 5kV, 5A electrode and 0.3Pa, 30℃ for 5 minutes to complete nitrogen plasma treatment. The hydroxyapatite dispersion obtained after the nitrogen plasma treatment is placed in a freeze dryer to remove excess water and whisker-like bio-template to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0054] Example 2

[0055] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0056] S1. Preparation of whisker-shaped bio-template: 0.5 g of bovine insulin was dissolved in 100 ml of 1 mol / L hydrochloric acid solution and adjusted to pH 2.0, heated to 70° C., maintained for 4 h, and then aged at room temperature to obtain whisker-shaped bio-template.

[0057] S2. Preparation of hydroxyapatite with bone-like structure: 200 mL of 0.05 mol / L calcium phosphate solution and 75 mL of 0.10 mol / L calcium hydrogen phosphate solution were mixed evenly, PBS was used as a pH regulator to adjust the pH to 7.4, and a microwave ultrasonic synergistic cell lysator with a microwave power of 600 W and an ultrasonic frequency of 160 kHz was used to react at 150° C. and a reaction pressure of 1.5 MPa for 48 h. The hydroxyapatite with bone-like structure was dried and ground.

[0058] S3, preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: the hydroxyapatite prepared in S2 and 5g of silane coupling agent KH560 are added to 250ml of acetic acid solution with a pH of 4.0 and stirred at 80°C for 1h. The hydroxyapatite dispersion treated with the silane coupling agent is placed in a muffle furnace and calcined at 700°C for 12h. After removing excess water and whisker-like biological templates, high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers are obtained. Figure 2 shown.

[0059] Example 3

[0060] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0061] S1. Preparation of whisker-shaped bio-template: 50 ml of 10% wild-type TMV solution was added to 200 ml of 5 wt % sodium phosphate solution, and the pH was adjusted to 7.0 with PBS buffer to obtain whisker-shaped bio-template.

[0062] S2. Preparation of hydroxyapatite with bone-like structure: evenly mix 250 mL of 0.05 mol / L calcium chloride solution and 75 mL of 0.10 mol / L sodium dihydrogen phosphate solution, adjust the pH to 8.0 using PBS as a pH regulator, react at 240°C and 5 MPa reaction pressure using a microwave ultrasonic synergistic crusher with a microwave power of 600 W and an ultrasonic frequency of 150 kHz for 5 min, dry and grind to obtain hydroxyapatite with bone-like structure.

[0063] S3, preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: 2.5 g of citric acid and 2.5 g of stearic acid were added to the hydroxyapatite dispersion obtained in S2 and stirred at 55° C. for 2 h. After stirring, the obtained hydroxyapatite dispersion was heat-treated at 170° C. for 8 h, spray-dried, and excess water and whisker-like biotemplates were removed to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0064] Example 4

[0065] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0066] S1. Preparation of whisker-shaped bio-template: 250 ml of calf thymus double-stranded DNA molecule with a mass concentration of 0.2% was dissolved in 250 ml of water after high pressure homogenization at 50 MPa and 25° C., and heated and stirred at 50° C. for 1 h to form a transparent solution to obtain a whisker-shaped bio-template.

[0067] S2. Preparation of hydroxyapatite with bone-like structure: 200 mL of 0.02 mol / L calcium phosphate solution and 15 mL of 0.2 mol / L trisodium phosphate solution were mixed evenly, the pH was adjusted to 7.5 using MOPS as a pH regulator, and a microwave ultrasonic chemical reactor with a microwave power of 800 W and an ultrasonic frequency of 130 kHz was used to react at 150° C. and a reaction pressure of 5 MPa for 25 min. The hydroxyapatite with bone-like structure was dried and ground.

[0068] S3. Preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: Place hydroxyapatite in an electrode vacuum chamber and treat it for 5 minutes at 5 kV, 5A electrode, 0.3 Pa, and 30°C to complete nitrogen plasma treatment. After the nitrogen plasma treatment, the hydroxyapatite dispersion obtained is dried and mechanically ground to remove excess water and whisker-like biological templates to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0069] Example 5

[0070] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0071] S1. Preparation of whisker-shaped bio-template: 0.5 g of bovine insulin was dissolved in 100 ml of 1 mol / L hydrochloric acid solution and adjusted to pH 2, heated to 70° C., maintained for 4 h, and then aged at room temperature to obtain whisker-shaped bio-template.

[0072] S2. Preparation of hydroxyapatite with bone-like structure: evenly mix 250 mL of 0.05 mol / L calcium nitrate solution and 50 mL of 0.15 mol / L disodium hydrogen phosphate solution, adjust the pH to 7.8 with acetic acid as a pH regulator, and use a microwave ultrasonic synergistic digestion apparatus with a microwave power of 1000 W and an ultrasonic frequency of 100 kHz to react at 100°C and a reaction pressure of 1 MPa for 24 hours. Dry and grind to obtain hydroxyapatite with bone-like structure.

[0073] S3. Preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: 5 g of bone-like hydroxyapatite was mixed with 50 ml of 1 mol / L magnesium chloride solution, stirred at 300 rpm for 24 h using a magnetic stirrer at room temperature, and ultrasonically dispersed at 750 W for 20 min to form a magnesium nanoparticle-doped hydroxyapatite dispersion. The magnesium nanoparticle-doped hydroxyapatite dispersion was electrostatically sprayed at 7 kV and a working distance of 4 mm, and the excess water and whisker-shaped biological template were removed to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0074] Example 6

[0075] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0076] S1. Preparation of whisker-shaped bio-template: 50 ml of 10% wild-type TMV solution was added to 200 ml of 5 wt % sodium phosphate solution, and the pH was adjusted to 7.0 with PBS buffer to obtain whisker-shaped bio-template.

[0077] S2. Preparation of hydroxyapatite with bone-like structure: 250 mL of 1 mol / L disodium calcium ethylenediaminetetraacetic acid solution and 62.5 mL of 2 mol / L sodium dihydrogen phosphate solution were mixed evenly, PBS was used as a pH regulator to adjust the pH to 8.0, and a microwave ultrasonic co-crusher with a microwave power of 800 W and an ultrasonic frequency of 150 kHz was used to react at 200° C. and a reaction pressure of 5 MPa for 1 h. The hydroxyapatite with bone-like structure was dried and ground.

[0078] S3, preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: 1.67 g of citric acid and 3.33 g of stearic acid were added to the hydroxyapatite dispersion obtained in S2 and stirred at 55°C for 2 h. After stirring, the obtained hydroxyapatite dispersion was heat-treated at 170°C for 8 h, spray-dried, and excess water and whisker-shaped biotemplates were removed to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0079] Example 7

[0080] A high-strength and high-bioactive hydroxyapatite nanowhisker with a bone-like structure and a preparation method thereof, comprising the following steps:

[0081] S1. Preparation of whisker-shaped bio-template: 50 ml of 10% wild-type TMV solution was added to 200 ml of 5 wt % sodium phosphate solution, and the pH was adjusted to 7.0 with PBS buffer to obtain whisker-shaped bio-template.

[0082] S2. Preparation of hydroxyapatite with bone-like structure: evenly mix 250 mL of 0.5 mol / L calcium chloride solution and 167 mL of 1.5 mol / L sodium dihydrogen phosphate solution, adjust the pH to 8.0 using PBS as a pH regulator, and react for 1 h at 200°C and 5 MPa reaction pressure using a microwave ultrasonic synergistic crusher with a microwave power of 800 W and an ultrasonic frequency of 150 kHz. Dry and grind to obtain hydroxyapatite with bone-like structure.

[0083] S3. Preparation of high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers: Place hydroxyapatite in an electrode vacuum chamber and treat it for 5 minutes at 5 kV, 5A electrode, 0.3 Pa, and 30°C to complete nitrogen plasma treatment. After the nitrogen plasma treatment, the hydroxyapatite dispersion obtained is dried and mechanically ground to remove excess water and whisker-like biological templates to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0084] Comparative Example 1

[0085] The method of Example 1 is basically adopted to prepare bone-like hydroxyapatite nanowhiskers with high strength and high biological activity. The difference is that this comparative example does not use biological macromolecules as templates. The specific preparation steps are as follows.

[0086] S1. Evenly mix 100 ml of 0.1% polyethylene glycol template, 250 ml of 0.01 mol / L calcium phosphate solution and 75 ml of 0.02 mol / L potassium dihydrogen phosphate solution, adjust the pH to 7.0 using Tris as a pH regulator, and use a microwave ultrasonic synergistic extractor with a microwave power of 800 W and an ultrasonic frequency of 120 kHz at 100°C and a reaction pressure of 1 MPa for 20 min. Dry and grind to obtain hydroxyapatite with a bone-like structure.

[0087] S2. Place the hydroxyapatite in an electrode vacuum chamber and treat it at 5 kV, 5A electrode, 0.3 Pa, 30°C for 5 minutes to complete the nitrogen plasma treatment. The hydroxyapatite obtained after the nitrogen plasma treatment is placed in a freeze dryer to remove excess water to obtain bone-like hydroxyapatite nanowhiskers.

[0088] Comparative Example 2

[0089] The method of Example 2 is basically adopted to prepare bone-like hydroxyapatite nano whiskers with high strength and high biological activity. The difference is that this comparative example does not use ultrasonic external field assistance. The specific preparation steps are as follows.

[0090] S1. Dissolve 0.5 g of bovine insulin in 100 ml of 1 mol / L hydrochloric acid solution and adjust the pH to 2.0. Heat to 70° C., keep for 4 hours, and then age at room temperature to obtain a whisker-like bio-template.

[0091] S2. Evenly mix 200 ml of 0.05 mol / L calcium phosphate solution and 75 ml of 0.10 mol / L calcium hydrogen phosphate solution, adjust the pH to 7.4 using PBS as a pH regulator, and react for 48 hours at 150°C and 1.5 MPa reaction pressure using a microwave chemical reactor with a microwave power of 600 W. Dry and grind to obtain hydroxyapatite with a bone-like structure.

[0092] S3, adding the hydroxyapatite prepared in S2 and 5g of silane coupling agent KH560 to 250ml of acetic acid solution with a pH of 4.0, stirring at 80°C for 1h, filtering and drying. The hydroxyapatite dispersion treated with the silane coupling agent is placed in a muffle furnace and calcined at 700°C for 12h, and then excess water and whisker-like bio-template are removed to obtain bone-like hydroxyapatite nanowhiskers.

[0093] Comparative Example 3

[0094] The method of Example 3 was basically adopted to prepare bone-like hydroxyapatite nanowhiskers with high strength and high biological activity. The difference was that microwave heating was not performed in this comparative example. The specific preparation steps were as follows.

[0095] S1. Dissolve 50 ml of wild-type TMV with a mass concentration of 10% in 200 ml of 5 wt% sodium phosphate solution, and adjust the pH to 7 with PBS regulator to obtain a whisker-shaped biological template.

[0096] S2. Evenly mix 25 ml of 0.05 mol / L calcium chloride solution and 75 ml of 0.10 mol / L sodium dihydrogen phosphate solution, adjust the pH to 8.0 using PBS as a pH regulator, and react for 5 minutes at 240°C and 5 MPa reaction pressure in a hydrothermal reactor, accompanied by the action of an ultrasonic extractor with a frequency of 150 kHz, to obtain hydroxyapatite with a bone-like structure by drying and grinding.

[0097] S3. Add 2.5 g of citric acid and 2.5 g of stearic acid to the hydroxyapatite dispersion obtained in S2 and stir at 55° C. for 2 h. After stirring, heat treat the hydroxyapatite at 170° C. for 8 h, spray dry the obtained hydroxyapatite to remove excess water and whisker-like biotemplate to obtain bone-like hydroxyapatite nanowhiskers.

[0098] Comparative Example 4

[0099] The method of Example 4 was basically adopted to prepare bone-like hydroxyapatite nano whiskers with high strength and high biological activity. The difference was that this comparative example did not undergo surface treatment. The specific preparation steps were as follows.

[0100] S1. Dissolve 250 ml of calf thymus double-stranded DNA molecules with a mass concentration of 0.2% in 250 ml of water after high-pressure homogenization at 50 MPa and 25° C., heat and stir at 50° C. for 1 hour to form a transparent solution to obtain a whisker-shaped biological template.

[0101] S2. Evenly mix 200 ml of 0.02 mol / L calcium phosphate solution and 15 ml of 0.2 mol / L trisodium phosphate solution, use MOPS as a pH regulator to adjust the pH to 7.5, use a microwave ultrasonic chemical reactor with a microwave power of 800 W and an ultrasonic frequency of 130 kHz to react for 25 minutes at 150° C. and a reaction pressure of 5 MPa to obtain hydroxyapatite with a bone-like structure; dry and mechanically grind the hydroxyapatite dispersion to obtain bone-like hydroxyapatite nanowhiskers.

[0102] Comparative Example 5

[0103] The method of Example 5 was basically adopted to prepare bone-like hydroxyapatite nanowhiskers with high strength and high biological activity. The difference was that ultrasonic treatment was not performed in this comparative example. The specific preparation steps were as follows.

[0104] S1. Dissolve 0.5 g of bovine insulin in 100 ml of 1 mol / L hydrochloric acid solution and adjust the pH to 2. Heat to 70° C., keep for 4 hours, and then age at room temperature to obtain a whisker-like bio-template.

[0105] S2. Evenly mix 250 mL of 0.05 mol / L calcium nitrate solution and 50 mL of 0.15 mol / L disodium hydrogen phosphate solution, adjust the pH to 7.8 using acetic acid as a pH regulator, and react for 24 hours at 100°C and 1 MPa reaction pressure using a microwave ultrasonic synergistic digestion apparatus with a microwave power of 1000 W. Dry and grind to obtain hydroxyapatite with a bone-like structure.

[0106] S3, 5g of bone-like hydroxyapatite was mixed with 50ml of 1mol / L magnesium chloride solution, stirred at 300 rpm for 24h with a magnetic stirrer at room temperature, and ultrasonically dispersed at 750W for 20min to form a magnesium nanoparticle-doped hydroxyapatite dispersion. The magnesium nanoparticle-doped hydroxyapatite dispersion was electrostatically sprayed at 7kV and a working distance of 4mm, and excess water and whisker-like biological templates were removed to obtain high-strength and high-bioactive bone-like hydroxyapatite nanowhiskers.

[0107] Structural characterization: The hydroxyapatite nanowhiskers were structurally characterized using field emission scanning electron microscopy (FESEM, HITACHI SU8220, Japan) and transmission electron microscopy (TEM, FEI, USA) with reference to the International Journal of Biological Macromolecules (Issue 226, 2022, page 1273), and the diameter and aspect ratio of the nanowhiskers were calculated based on the characterized images.

[0108] Mechanical properties test: Referring to the "Journal of the Mechanical Behavior of Biomedical Materials" (Issue 133, 2022, page 105306), the elastic modulus, hardness and fracture toughness of nanohydroxyapatite were tested using the NanoIndenterXP system (Keysight Technologies, USA), with load and displacement resolutions of 1 nN and 0.1 nm, respectively.

[0109] Cell proliferation rate test: The cell proliferation rate was determined according to the CCK-8 method. MC3T3-E1 cells were first cultured in high-glucose DMEM cell culture medium (containing 10% fetal bovine serum + 1% double antibody) at 25 cm 2 Inoculate cells in a cell culture flask at 37°C and place it in a cell culture incubator containing 5% CO2 by volume. Change the medium every 2 to 3 days. When the cells cover about 80% of the bottom of the flask, add an appropriate amount of trypsin for digestion. After centrifugation, resuspend in high-glucose DMEM cell culture medium and passage at a ratio of 1:3. MC3T3-E1 cells were cultured at 2×10 3 / well density was inoculated into a 96-well plate. After culturing in a cell culture incubator for 24 hours, the normal control group replaced the normal cell culture medium, and each experimental group replaced the culture medium with the corresponding extract, and then the medium was changed every two days. The Cell Counting Kit-8 (CCK-8) kit was used to detect the proliferation activity of the cells after the first and seventh days of culture. The specific operation steps are: take out the 96-well plate at a predetermined time point, discard the culture medium, add 100 μL of cell culture medium containing 10% CCK-8 to each well, and then place it in a cell culture incubator at 37°C and a CO2 volume fraction of 5% for 2 hours, and use a microplate reader to measure the absorbance value (OD) at 450nm. The seven-day proliferation rate is calculated according to (OD D7 -OD D1 ) / OD D1 calculate.

[0110] Table 1 Morphological characteristics, mechanical properties and bioactivity test results

[0111]

[0112] Table 1 compares the mechanical properties and bioactivity strength of the hydroxyapatite whiskers obtained in the examples and comparative examples. The nanohydroxyapatites of Examples 1-5 are similar in morphology to the hydroxyapatite of human bone (diameter is 15.5nm-34.8nm, aspect ratio is 3.2-7.5), and are more compatible with the physiological environment of human bone than Comparative Examples 1-5. As for mechanical properties, Examples 1-5 show good mechanical strength, elastic modulus is 95GPa-215GPa, hardness is 1.5GPa-3.8GPa, fracture toughness is 0.035MPa·m 1 / 2 ~0.095MPa·m 1 / 2 , which is about 2 times that of Examples 1-5, to ensure that it can effectively withstand physiological loads and promote the integration of bone tissue during the repair process. It is also of great significance that the seven-day cell proliferation rate of Examples 1-5 after adding cell culture medium is 1.987 to 3.118, which is about 1.4 times that of Examples 1-5, which can effectively promote cell adhesion, proliferation and differentiation, while providing a suitable microenvironment to promote the formation of new bone. This shows that the present method can improve the mechanical properties and biological activity of hydroxyapatite whiskers, and prepare high-strength and high-activity nano-hydroxyapatite whiskers with bone-like structures.

[0113] This shows that the preparation method of the present invention significantly improves the mechanical properties and bioactivity of hydroxyapatite, which is likely due to: (1) the whisker morphology and composition of nano-hydroxyapatite prepared by the biological template are very similar to the hydroxyapatite in human bones; (2) the surface modification treatment makes hydroxyapatite have higher mechanical properties and bioactivity; (3) the ultrasonic external field and microwave assistance give hydroxyapatite more energy for nucleation and growth.

[0114] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0115] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing bone-like hydroxyapatite nanowhiskers induced by biological templates, characterized in that: The following steps are involved: The whisker-shaped biomacromolecules are dispersed to obtain a whisker-shaped biotemplate; After mixing a phosphate solution and a calcium salt solution, adjusting the pH to 7-8 to obtain a precursor solution, mixing the precursor solution with a whisker-shaped biological template, and subjecting the mixture to ultrasonic microwave treatment, during which hydroxyapatite nucleates and grows to obtain hydroxyapatite nanowhiskers; The hydroxyapatite nano whiskers are subjected to surface modification treatment to improve the mechanical properties of the hydroxyapatite nano whiskers, thereby obtaining bone-like hydroxyapatite nano whiskers.

2. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The mass ratio of calcium salt to whisker-shaped bio-template is 10-50:

1.

3. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: In the precursor solution, the molar ratio of phosphorus element to calcium element is 1:0.5-2; the concentration of the calcium salt solution is 0.01mol / L-1mol / L, and the concentration of the phosphate solution is 0.02mol / L-2mol / L.

4. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The ultrasonic frequency of the ultrasonic microwave treatment is 100kHz to 160kHz, the microwave power is 600W to 1000W, the treatment temperature is 100°C to 240°C, the treatment time is 5min to 48h, and the reaction pressure is 1MPa to 5MPa.

5. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The surface modification treatment is at least one of nitrogen plasma treatment, silane coupling agent treatment, citric acid and stearic acid modification, heat treatment and metal nanoparticle doping.

6. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The whisker-shaped biomacromolecules are pancreatic islet fibers, chain DNA or linear viruses.

7. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The calcium salt is at least one of calcium phosphate, calcium hydrogen phosphate, calcium dihydrogen phosphate, calcium chloride, calcium nitrate and calcium disodium edetate.

8. The method for preparing bone-like hydroxyapatite nanowhiskers by biological template induction according to claim 1, characterized in that: The phosphate is at least one of potassium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, calcium hydrogen phosphate and calcium phosphate.

9. Bone-like hydroxyapatite nanowhiskers prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bone-like hydroxyapatite nanowhiskers according to claim 9 in preparing bone repair materials and bone regeneration materials.